2004
DOI: 10.1002/eat.20038
|View full text |Cite
|
Sign up to set email alerts
|

Anger and bulimic psychopathology: Gender differences in a nonclinical group

Abstract: Men appear to engage in bulimic behaviors to reduce anger states, whereas women appear to use such behaviors to reduce the likelihood of anger states from arising. Further experimental validation of these findings is required in both clinical and nonclinical groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 13 publications
0
22
2
Order By: Relevance
“…In the study of Meyer et al [61] , bulimic attitudes were associated with state anger in men and with anger suppression in women. In the study of Milligan and Waller [62] , conducted in a female sample, binge eating was associated with suppression of anger, whereas vomiting was associated with high levels of state anger.…”
Section: Anger and Edsmentioning
confidence: 90%
“…In the study of Meyer et al [61] , bulimic attitudes were associated with state anger in men and with anger suppression in women. In the study of Milligan and Waller [62] , conducted in a female sample, binge eating was associated with suppression of anger, whereas vomiting was associated with high levels of state anger.…”
Section: Anger and Edsmentioning
confidence: 90%
“…However, when compared to females, there are relatively few studies that have assessed the possible impact of mass media exposure to male beauty ideals on men's health. Nevertheless, the existing studies appear to coincide in that men are increasingly expected to attain slender and muscular bodies (Farquhar & Wasylkiw, 2007;Grilo & Masheb, 2005;Hospers & Jansen, 2005;Keel & Gravener, 2008;Meyer, Leung, Waller, Perkins, Paice, & Mitchell, 2005), at times, through extreme weight control behaviours such as over-exercise and steroid use (Hatoum & Belle, 2004). In the study by Hatoum and Belle (2004), the authors likewise reported an association between magazine exposure to this type of content and concerns regarding body-building, fitness, beauty and dietetic products along with low self-esteem which was associated significantly to these weight concerns.…”
Section: Introductionmentioning
confidence: 99%
“…For example, initial findings suggest that anger and aggression might be associated with bulimic behaviors in men. 23,24 No other studies to date have examined relationships between aggressive behaviors, delinquency, or socially intrusive behavior and eating pathology in males. These types of externalizing behaviors, largely ignored in the field, might play a significant role in the expression or development of eating pathology in males versus females.…”
Section: Introductionmentioning
confidence: 99%